PENINGKATAN KEMAMPUAN BERHITUNG ANAK USIA DINI MELALUI MEDIA DADU ANGKA DI TK ALLIM BABAT LAMONGAN - Titin Shofiyah (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2024)
This study aims to improve early childhood counting skills through the use of number dice media at TK Allim Babat Lamongan. The research employed Classroom Action Research (CAR) consisting of two cycles involving 15 children from Group A in the 2023/2024 academic year. Data were collected through observation, documentation, and assessment of learning outcomes, then analyzed descriptively and quantitatively. The findings revealed an improvement in children’s counting ability from 45.3% in the pre-cycle to 61.5% in cycle I and significantly increased to 92.2% in cycle II. The number dice media proved effective in enhancing counting skills interactively and joyfully.